Red parka Mary - Eyvindson, Peter; Brynjolson, Rhian (Winnipeg : Pemmican Publishers, 1996)
The seven year old First Nations boy who was once afraid of his elderly neighbor learns that she is really very friendly and has much to teach him. After he gives her the gift of a red parka, she promises to give him a fantastic gift on Christmas Day.
University of Alberta copy in the Canadian Children's Book Centre Depository Collection.
Keywords: Indians of North America -- Juvenile fiction; Friendship -- Juvenile fiction